Erratum to “Two-Way Mixed RF/FSO Relaying System in the Presence of Co-Channel Interference” - Zhuo Wang; Wenxiao Shi; Wei Liu (IEEE Photonics Journal, 2019)
Presents corrections to the paper, “Two-way mixed RF/FSO relaying system in the presence of co-channel interference,” (Wang, Z., et al), IEEE Photon. J., vol. 11, no. 2, Apr. 2019, Art. no. 7902516.